(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Balicab Transportation Services in Badung Regency is one of the businesses operating in the transportation services sector whose business activities cannot be separated from increasingly competitive market conditions. Therefore, it is necessary to implement a marketing strategy that takes into account perceived usefulness, perceived risk and quality of information to create buying interest. The aim of this research is to determine the influence of perceived usefulness, perceived risk, and quality of information on buying interest. The population in this study are users of the Balicab Transportation Service in Badung Regency, the exact number of which is not known. The sample size was determined 5 to 10 times the number of indicators so that a sample of 105 respondents was obtained. Hypothesis testing is carried out using the classic assumption test, multiple linear regression analysis. From the results of the analysis, it can be concluded that: 1. perceived usefulness on buying interest, 2. perceived risk on buying interest, 3. information quality on buying interest, 4. perceived usefulness, perceived risk and information quality on buying interest.